Folate (vitamin B9) - Fairweather-Tait, Susan (Henry Stewart Talks, 2026)
Folate function in body, Food sources of folate, Absorption and metabolism of folate, Effect of genotype on folate metabolism, Deficiency and excess of folate, Neural tube defects, Dietary reference values for folate in adults